2012
DOI: 10.7439/ijbar.v3i4.350
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticonvulsant Screening of Some Novel Derivatives of Substituted Benzofuran

Abstract: A series of N- (2-benzoylbenzofuran-3-yl)-4-(substituted)butanamides (IIIa-f) were synthesized in good yield and evaluated for anticonvulsant activity and neurotoxic study. The identity of the synthesized compounds was confirmed on the basis of their elemental analysis and spectral data. In anti-MES test compounds IIIb, IIIc, IIId and IIIf showed potent activity. Compounds IIIa and IIIe were less toxic as compared with the standard drug phenytoin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In addition, benzofuran derivatives have been reported to possess a wide variety of pharmacological properties, viz. anti‐inflammatory , anticancer , antimicrobial , antioxidant , antitubercular , anti‐TB , anticonvulsant , anti‐AChE , and antagonistic activities. On the other hand, literature survey revealed that pyrazoline derivatives possess a broad spectrum of biological activities including anticancer, anti‐inflammatory, antihypotensive, antidepressant, anticonvulsant, antimicrobial, and antitubercular activities .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, benzofuran derivatives have been reported to possess a wide variety of pharmacological properties, viz. anti‐inflammatory , anticancer , antimicrobial , antioxidant , antitubercular , anti‐TB , anticonvulsant , anti‐AChE , and antagonistic activities. On the other hand, literature survey revealed that pyrazoline derivatives possess a broad spectrum of biological activities including anticancer, anti‐inflammatory, antihypotensive, antidepressant, anticonvulsant, antimicrobial, and antitubercular activities .…”
Section: Introductionmentioning
confidence: 99%